2014
DOI: 10.1523/jneurosci.0326-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Presynaptic Ca2+, Synaptic Plasticity and Contextual Fear Conditioning by a N-terminal β-Amyloid Fragment

Abstract: Soluble ␤-amyloid has been shown to regulate presynaptic Ca 2ϩ and synaptic plasticity. In particular, picomolar ␤-amyloid was found to have an agonist-like action on presynaptic nicotinic receptors and to augment long-term potentiation (LTP) in a manner dependent upon nicotinic receptors. Here, we report that a functional N-terminal domain exists within ␤-amyloid for its agonist-like activity. This sequence corresponds to a N-terminal fragment generated by the combined action of ␣-and ␤-secretases, and reside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
81
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(87 citation statements)
references
References 44 publications
5
81
1
Order By: Relevance
“…The APLP1 protein shows the highest presence at the cell surface among all APP protein family members (Kaden et al, 2009; Mayer et al, 2016). As indicated Figure 2B depicts the APP protein family function at the presynaptic site, where the Aß, Aß-15 and possibly the APPsα domain interfere with glutamate release by activating nAChRs and enhancing intracellular Ca 2+ levels (Puzzo et al, 2008; Wang Z. et al, 2012; Lawrence et al, 2014). It is further hypothesized that homodimerized APP acts as a G-Protein coupled receptor which is activated by Aß and might be involved in neurotransmitter release following enhanced Ca 2+ influx.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The APLP1 protein shows the highest presence at the cell surface among all APP protein family members (Kaden et al, 2009; Mayer et al, 2016). As indicated Figure 2B depicts the APP protein family function at the presynaptic site, where the Aß, Aß-15 and possibly the APPsα domain interfere with glutamate release by activating nAChRs and enhancing intracellular Ca 2+ levels (Puzzo et al, 2008; Wang Z. et al, 2012; Lawrence et al, 2014). It is further hypothesized that homodimerized APP acts as a G-Protein coupled receptor which is activated by Aß and might be involved in neurotransmitter release following enhanced Ca 2+ influx.…”
Section: Resultsmentioning
confidence: 99%
“…It functions via binding to presynaptic APP homodimers (Fogel et al, 2014) or by activating α7-nAChRs (Tong et al, 2011). The study by Lawrence et al (2014) highlighted that the N-terminal domain of Aß contains this agonist-like activity of the Aß peptide. It was further suggested that successive α- and ß-secretase activity will release the short functional domain, named Aß1–15 (or Aß1–16, Portelius et al, 2011).…”
Section: Aß Dominantly Acts At the Presynapsementioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms underlying the physiological role of Aβ involved K + and Ca 2+ ion channels and several key receptors for synaptic function such as glutamatergic and cholinergic receptors. In particular, we have focused on nAchRs because i) they play a fundamental role in learning and memory in physiological conditions (Levin, 2002; Albuquerque et al, 2009; Yakel et al, 2013; 2014); ii) the cholinergic deficit is closely related to the pathogenesis of AD (Levey, 1996; Clader and Wang, 2005; Oddo and La Ferla, 2006; Yakel, 2013); iii) Aβ has a picomolar affinity for α7-nAChRs (Wang et al, 2000); iv) Aβ modulate α7-nAChR function (Dougherty et al, 2003; Small et al, 2007; Khan et al, 2010; Lawrence et al, 2014) and it is able to act as an agonist or an antagonist depending upon the dose, as previously discussed (Dineley et al, 2002; Grassi et al, 2003; Fodero et al, 2004). [Please see Dineley, 2007 for a review on Aβ-nAChR interaction in health and disease].…”
Section: Aβ Between Pathology and Physiologymentioning
confidence: 99%
“…In our works (Puzzo et al, 2008; 2011) we have shown that a pharmacological or genetic blockage of α7-nAChRs resulted in inhibition of the Aβ-induced increase of post-tetanic potentiation, LTP and memory; moreover the inhibition of endogenous Aβ did not affect synaptic plasticity in α7-nAChR-KO, supporting the hypothesis that the physiological effect of low Aβ concentrations is mediated by α7-nAChRs. A recent paper (Lawrence et al, 2014) has shown that an Aβ N-terminal fragment exerts a highly potent agonist-like action on nicotinic receptors, boosting LTP and contextual fear memory that, in turn, was attenuated by co-administration of a nicotinic antagonist.…”
Section: Aβ Between Pathology and Physiologymentioning
confidence: 99%